Curcuminoids as Modulators of EMT in Invasive Cancers: A Review of Molecular Targets With the Contribution of Malignant Mesothelioma Studies - Pouliquen, Daniel L.; Boissard, Alice; Henry, Cécile; Coqueret, Olivier; Guette, Catherine (Frontiers in Pharmacology, 2022)
Curcuminoids, which include natural acyclic diarylheptanoids and the synthetic analogs of curcumin, have considerable potential for fighting against all the characteristics of invasive cancers. The epithelial-to-mesenchymal transition (EMT) is a fundamental process for embryonic morphogenesis, however, the last decade has confirmed it orchestrates many features of cancer invasiveness, such as tumor cell stemness, metabolic rewiring, and drug resistance. A wealth of studies has revealed EMT in cancer is in fact driven by an increasing number of parameters, and thus understanding its complexity has now become a cornerstone for defining future therapeutic strategies dealing with cancer progression and metastasis. A specificity of curcuminoids is their ability to target multiple molecular targets, modulate several signaling pathways, modify tumor microenvironments and enhance the host’s immune response. Although the effects of curcumin on these various parameters have been the subject of many reviews, the role of curcuminoids against EMT in the context of cancer have never been reviewed so far. This review first provides an updated overview of all EMT drivers, including signaling pathways, transcription factors, non-coding RNAs and tumor microenvironment components, with a special focus on the most recent findings. Secondly, for each of these drivers the effects of curcumin / curcuminoids on specific molecular targets are analyzed. Finally, we address some common findings observed between data reported in the literature and the results of investigations we conducted on experimental malignant mesothelioma, a model of invasive cancer representing a useful tool for studies on EMT and cancer.